2016
DOI: 10.3121/cmr.2016.1306
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Health in Adulthood in a Rural Population-Based Sample

Abstract: Background: Adverse childhood experiences (ACEs), including emotional abuse, substance abuse in the household, separation or divorce, physical abuse, violence between adults, mental illness in the household, sexual abuse, or incarceration of a household member, have the potential to profoundly impact health and well-being in adulthood. To assess whether previously reported relationships between ACEs and health outcomes withstand validation, we conducted a community-based ACE study with the unique capacity to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 43 publications
6
36
3
4
Order By: Relevance
“…The largest number of adolescents in this study was exposed to neglect and multiple abuse, which is in line with foreign research data, where it has been observed that an increasing number of scientific research data indicate that some types of child abuse do not appear in isolation [21,22,23] . The results of this study indicate that neglect and physical abuse are the most commonly associated, which was observed by the scientists in one foreign study, while in the second · br.…”
Section: Discussionsupporting
confidence: 90%
“…The largest number of adolescents in this study was exposed to neglect and multiple abuse, which is in line with foreign research data, where it has been observed that an increasing number of scientific research data indicate that some types of child abuse do not appear in isolation [21,22,23] . The results of this study indicate that neglect and physical abuse are the most commonly associated, which was observed by the scientists in one foreign study, while in the second · br.…”
Section: Discussionsupporting
confidence: 90%
“…Other chronic medical conditions might be associated as well. However, recent general population studies showed ambiguous results regarding the relationship between ACE and somatic illness at adult age (Iniguez, 2016;Bellis et al, 2015). A recent systematic review in the general population found weak associations with obesity or Diabetes Mellitus for an ACE score of four or more, and moderate associations with cancer, cardiac or respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Parental separation and parental poor mental health are important forms of adverse childhood experiences, with prevalence rates of 23% and 19%, respectively (Anda et al, 2006). Adverse childhood experiences are known to be associated with an increased risk of poor physical and mental health in adulthood (Iniguez and Stankowski, 2016). Also, there is a growing body of evidence suggesting an association between childhood adversities and sleep disorders in adulthood (Bader et al, 2007;Chapman et al, 2011;Ramsawh et al, 2011;Chapman et al, 2013;Kajeepeta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%